Electrical vestibular nerve stimulation in the management of pain in the patients with temporomandibular disorders: A pilot study - Sai Sailesh Kumar G,; Namit Garg,; Nitu Kumari,; Anita Choudhary,; Sudhir Gawarikar,; Rohit Singh Chouhan,; Dharampal Singh Chouhan,; Mahadik V K, (Asian Journal of Medical Sciences, 2022)
Background: It is hypothesized that electrical vestibular stimulation may be an effective adjunctive therapy in the management of Temporomandibular disorder (TMD). Aims and Objectives: The aim of the present study is to assess the effectiveness of electrical vestibular nerve stimulation (VeNS) in the management of pain in patients with temporomandibular disorders. Materials and Methods: A total of 24 male and female participants newly diagnosed with TMD were recruited after obtaining the written informed consent. VeNS was administered for 4 weeks. Each daily session was for an hour (1 h), with three sessions being carried out each week. The pain was assessed using a numerical pain rating scale. The JFLS-8 is a short form for measuring global functional limitations of the jaw. The DASS-21 questionnaire is comprised of three self-reported scales to measure negative emotional states of depression, anxiety, and stress. Results: Age, height, weight and, BMI were not significantly different between the control and intervention groups (Table 1). There was a significant decrease in the pain score in the intervention group when compared with the control group (P<0.001). Jaw function score was significantly improved followed by the intervention in the intervention group (P<0.001). Depression scores were significantly decreased followed by the intervention in the intervention group (P<0.001). Anxiety scores were significantly decreased followed by the intervention in the intervention group (P<0.001). Stress scores were significantly decreased followed by the intervention in the intervention group (P<0.001). Conclusion: The study introduced new technology that is electrical VeNS for the management of pain. Electrical vestibular stimulation is effective in the management of pain and decreases the negative emotions that are depression, anxiety, and stress, and improves sleep quality in patients with temporomandibular disorders. The study recommends further detailed studies in this area to recommend electrical vestibular stimulation as adjunctive therapy for the management of pain.